Heterosis for seed yield and yield contributing traits in Sunflower (Helianthus annuus L.): Heterosis for seed yield and yield contributing traits in Sunflower (Helianthus annuus L.) - J V SHINDE; M K GHODKE; B D CHAUDHARI; K B GAIWAL (Journal of Oilseeds Research, 2023)
The present investigation on “Heterosis studies for seed yield and yield contributing traits in Sunflower (Helianthus annuus L.). four CMS & eight restorer lines were crossed in L x T design to produce 32 hybrids during kharif- 2021these 32 hybrids along with two checks were evaluated for days to 50 % flowering, day to maturity, plant height, head diameter, seed filling percentage, 100 seed weight, volume weight, hull content, seed yield/plant and oil content. The range of heterosis over best check LSFH-171 was from (-52.81)per cent CMS-47A x IR-1-1 to (30.67)per cent CMS-234A x MRHA-2. whereas for another check LSFH-35 was from (-50.88)per cent CMS-47A x IR-1-1 to (36.02)per cent CMS-234A x MRHA-2 for seed yield/plant. Among the hybrids CMS-234A X MRHA-2, CMS-249A X R/HA-1, CMS-47A X MRHA-2, CMS-234A X R/HA-1 and CMS-10A X MRHA-2 was most promising for seed yield /plant (g) on the basis ofper se performance, highest significant standard heterosis for seed yield and yield contributing traits.